Social innovation and social entrepreneurship: Uncovering themes, trends, and discourse - Carlos Sampaio; Jo\~ao Renato Sebasti\~ao (Administrative Sciences, 2024)
The world is marked by persistent and recurring socio-economic and environmental changes. The domains of social innovation and social entrepreneurship have gained prominence as catalysts for positive change and societal resilience. Despite the substantial body of literature assessing social innovation and social entrepreneurship, most studies address these topics through analyses of scientific production output or through systematic literature reviews. Conversely, the main objective of this paper is to conduct a thematic analysis of the existing scientific literature on social innovation and social entrepreneurship, published across various geographical contexts, to assess themes, trends, and discourse within these fields worldwide. Therefore, it synthesizes, analyzes, and evaluates the evolving landscape of social innovation and social entrepreneurship research over time, employing a sliding windows methodology. This approach divides the analyzed period into distinct times to meticulously track changes in themes and discourse over time. To accomplish this objective, this paper examines the evolving thematic dynamics of social innovation and social entrepreneurship within the scientific literature, serving as a driver and compelling researchers and practitioners to explore new dimensions in social innovation and social entrepreneurship. Evidence from the analysis is discussed, including the main theoretical and practical implications and proposals for future research. This paper emphasizes the importance of adaptive and resilient approaches within the domains of social innovation and social entrepreneurship and contributes to a deeper understanding of how social innovation and social entrepreneurship evolve and adapt over time, shedding light on the transformative potential of social innovation and social entrepreneurship.
Keywords: 350; nonprofit organizations; social entrepreneurship; social innovation; thematic analysis